Crystal and molecular structure of bis(N-(diethylcarbamothioyl)cyclohexane carboxamido)copper(II) complex - Ozer, Cemal Koray; Binzet, Gun; Arslan, Hakan (European Journal of Chemistry, 2020)
Herein, we describe the synthesis and characterization of bis(N-(diethylcarbamothioyl)cyclohexane carboxamido)copper(II) complex, cis-[Cu(L-κ2S,O)2], has been prepared by the reaction of N-(diethyl carbamothioyl)cyclohexanecarboxamide ligand with copper(II) acetate. The green colored crystals of the complex were obtained by slow evaporation of their dichloromethane:ethanol solution (2:1, v:v). The crystal structure of cis-[Cu(L-κ2S,O)2] was obtained by single-crystal X-ray diffraction. The crystal structure reveals an monoclinic C2 (no. 5) space group with cell parameters a = 14.848(3) Å, b = 10.543(2) Å, c = 10.511(2) Å, β = 123.84(3)°, V = 1366.7(7) Å3, Z = 2, T = 153(2) K, μ(MoKα) = 0.979 mm-1, Dcalc = 1.327 g/cm3, 4979 reflections measured (6.6° ≤ 2Θ ≤ 50.68°), 2243 unique (Rint = 0.0223, Rsigma = 0.0444) which were used in all calculations. The final R1 was 0.0225 (>2sigma(I)) and wR2 was 0.0490 (all data). The angular structural index parameter, τ4, is equal to 0.40, which confirms the distorted square planar geometry for the title compound. The puckering parameters (q2 = 0.015(3) Å, q3 = 0.576(3) Å, QT = 0.577(3) Å, θ = 1.6(3)° and φ = 20(11)°) of the title complex show that the cyclohexane ring adopts a chair conformation. The two ethyl groups of the diethyl amine group have anti-orientation with respect to one another. The crystal packing shows the molecules stacked in parallel sheets along [010], accompanied by C3-H3A···O1ⁱ (i -x, +y, 1-z) intermolecular contact.